Biomechanics of double poling when skiing on snow and using an ergometer - Linnamo, V.; Halonen, J.; Ohtonen, O.; Lemmettylä, T.; Lindinger, S. J.; Rapp, W.; Häkkinen, K. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Many studies exist about double poling in cross country skiing (e.g. Holmberg et al. 2005, Lindinger et al. 2009, Stöggl et al. 2006). Special ergometers have been used in training to simulate double poling, but there is a lack of knowledge whether the biomechanics of the movement are similar using ergometers as they are during natural skiing conditions. Therefore, the purpose of the present study was to compare cycle characteristics, force production and muscle activation between double poling on snow and double poling using an ergometer.